PERENCANAAN PEMELIHARAAN MOTOR DIESEL DENGAN METODE RCM (RELIABILITY CENTERED MAINTENANCE) PADA PLTG TELUK LEMBU PEKANBARU - Darno (Jurnal Surya Teknika, 2020)
Teluk Lembu Gas Power Plant (PLTG) is one type of power plant that uses the power of burning fuel and high pressure air. To be able to meet the needs of electrical energy on the island of Sumatra, especially in the Riau region,electricity production must not experience a decrease in productivity due to equipment damage. Obstacles that arise are frequent downtime unexpectedresulting in the production of electricity is interrupted or even to cause derating caused by damage to the operational when the engine is running. This study aims to provide recommendations for equipment maintenance andtime intervals optimal inspectionin the generator system. The research method used is Reliability Centered Maintenance (RCM) withanalysis quantitative. Where are the stages of implementing the RCM method, namely determining thecomponents criticalin the PLTG generator engine, determining thevalues, determining the Mean Time to Failure (MTTF) and Mean Time to Repair (MTTR)time interval optimal maintenance, and making a table of causes of damage to thecomponents generator engine. After analyzing it, it was found that thecomponent criticalof PLTG Teluk Lembu is the Diesel Motor. This is obtained based on the component with the highest frequency of damage, namely 13 damage during a period of 1 year. From the results of data processing, it is obtained that the MTTF value is 0.92441 hours and the MTTR value is 0.89014 hours. Theinspection time interval optimalis 25 days, so it is advisable to carry out Corrective and Preventive maintenance activities for Diesel Motorcycles periodically every 25 days (PM 25D) in order to increase the reliability of the Diesel Motor